Mechanisms to medicines: navigating drug repurposing strategies in Alzheimer’s disease - Khan, Sara Akhtar; Raza, Khushi; Tiwari, Prachi; El-Tanani, Mohamed; Rabbani, Syed Arman; Parvez, Suhel (Frontiers in Aging Neuroscience, 2026)
Alzheimer’s disease (AD) represents a continuously advancing neurodegenerative condition distinguished by the unremitting deterioration of cognitive abilities and memory impairment, which significantly hampers daily functioning of life. In the absence of disease modifying treatments, it continues to pose a significant global challenge. Though symptomatic treatment exists, the inherent complexity involved with AD pathogenesis related to Aβ plaques, neurofibrillary tangles, neuroinflammation, oxidative stress, etc. poses a tremendous challenge to developing drugs. With the incidence of AD increasing yearly globally, research into already existing pharmacological agents has the potential to uncover a brighter future for breakthroughs in treatment strategy. A primary strategy to accelerate the development of AD therapies is drug repurposing: determining a new use for an existing known medication. Following innovative approaches like high-throughput screening, AI-based techniques, a number of classes of drugs originally designed for other diseases are now being tested to modulate the complex pathology mechanisms in AD. This review focuses on the therapeutic promise of drug repurposing as adjunctive to the much-needed renaissance in AD therapies. The review continues to focus on some promising repurposed drug candidates, methodologies applied, and the evaluation of the present status of drugs in the clinic. Apart from the information regarding mechanisms involved in AD, this review also complements case studies, challenges, and limitations along with the various drug repurposing strategies for AD. By understanding and harnessing the potential of existing pharmacological agents, we can expand therapeutic options and improve patient outcomes.